Jawi writing in al-Quran and al-Sunnah subject at secondary school : issues and challenges - Amrina Rasyada Kamaruzaman; Nik Md Saiful Azizi Nik Abdullah; Rabi’atul Athirah Muhammad Isa @ Omar (Pusat Kelestarian Turath Islami, Fakulti Pengajian Islam, Universiti Kebangsaan Malaysia, 2021)
The objectives of this study are to identify issues and challenges in Jawi writing, know the students' performance in al-Quran and al-Sunnah subject, determine the level of student achievement in Jawi writing and relate the relationship between student achievement in Jawi writing and students performance in al-Quran and al-Sunnah subjects among secondary school students. This study used quantitative methods through survey questions distributed to students in four selected schools. Next, a test in writing Jawi and interviews with teachers experienced in the subjects of al-Quran and al-Sunnah were also implemented to support the results of the study through survey questions. The results of this study shows that there is no significant difference in the issues and challenges faced for Jawi writing in secondary schools. This issue calls for the commitment of all parties to play their part in preserving the heritage of the archipelago, reflecting the strong Islamic influence on life itself. The study also suggested the diversification of Jawi's writing activities in order to strengthen Jawi's writing skills and prevent them from losing time.